2013
DOI: 10.1002/jgrg.20057
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for microorganisms participating in Fe, Mn, and S biogeochemical cycling in two low‐temperature hydrothermal fields at the Southwest Indian Ridge

Abstract: [1] We examined two low-temperature hydrothermal deposits rich in Fe-Si-Mn collected from the recently discovered hydrothermal fields at the Southwest Indian Ridge using mineralogical, geochemical, and molecular biological techniques. The mineralogical and geochemical analyses indicated that the low-temperature hydrothermal fields would provide a warm and chemical species-rich habitat for chemosynthetic-based hydrothermal ecosystems. Analyses of 16S rRNA sequences showed that z-Proteobacteria, Pseudoalteromona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 146 publications
1
51
0
Order By: Relevance
“…It was found that there were no significant differences in microbial compositions between the hydrothermal plume samples and the ambient seawater (Li et al, ). Nevertheless, microorganisms (including bacterial and archaea) such as Fe, Mn, S oxidizers and reducers, and membrane lipids were abundant in the low‐temperature diffuse environment (Li et al, ; Pan et al, ; Peng et al, ). Therefore, organic matter from the nearby diffuse flow might be the most likely source of the ligands in Longqi hydrothermal plumes.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that there were no significant differences in microbial compositions between the hydrothermal plume samples and the ambient seawater (Li et al, ). Nevertheless, microorganisms (including bacterial and archaea) such as Fe, Mn, S oxidizers and reducers, and membrane lipids were abundant in the low‐temperature diffuse environment (Li et al, ; Pan et al, ; Peng et al, ). Therefore, organic matter from the nearby diffuse flow might be the most likely source of the ligands in Longqi hydrothermal plumes.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, much research has gone into an understanding of sedimentation on ocean ridges, especially metalliferous sediments generated by activity of submarine hydrothermal systems (Dekov et al, 2010;Edwards et al, 2011;Peng et al, 2011;Li et al, 2013). Hydrothermal umber deposits are fossiliferous, siliceous fine-grained, Fe-Mn-rich sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Niu et al (2015) also identified the thick crust (*10 km) beneath the segment center by wide-angle seismic reflection. Li et al (2013) reported the geochemical and molecular biological compositions of low-temperature hydrothermal deposits. Sun et al (2015) further investigated the mineralization of these deposits indicating the presence of Fe-oxidizing bacteria.…”
Section: Introductionmentioning
confidence: 99%